Influence of sulfate-reducing bacteria on the biocorrosion of mild steel coated with hybrid polyetherimide-ZnO or CuO bilayer composites - Rahali, Emna; El-Bassi, Leila; Bousselmi, Latifa; Alves, Marta M.; Montemor, Maria de Fátima; Akrout, Hanene (Comptes Rendus. Chimie)
Mild steel (MS) coated with protective bilayer hybrid coatings of polyetherimide, and ZnO/CuO was exposed to artificial treated wastewater (ATWW) inoculated with Desulfovibrio sp. (biotic system). Proteins from the extracellular polymeric substances (EPS) matrix of Desulfovibrio sp. responded to the coatings. PEI-CuO offered the highest performance against biocorrosion. The higher PEI-CuO resistivity value of $2.17× 10^{6}~Ω {· }cm^{2}$ contrasted with the decrease to $1.5× 10^{5}$ and $1.6× 10^{3}~Ω {· }cm^{2}$ for PEI-ZnO and PEI coatings, respectively. The one order of magnitude increased resistance of the biotic system, compared to sterilized ATWW (abiotic system), resulted from the protective nature of the bacterial biofilm.